On the psychology of the relation between optimism and risk taking - Thomas Dohmen; Simone Quercia; Jana Willrodt (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
In this paper, we provide an explanation for why risk taking is related to optimism. Using a laboratory experiment, we show that the degree of optimism predicts whether people tend to focus on the positive or negative outcomes of risky decisions. While optimists tend to focus on the good outcomes, pessimists focus on the bad outcomes of risk. The tendency to focus on good or bad outcomes of risk in turn affects both the self-reported willingness to take risk and actual risktaking behavior. This suggests that dispositional optimism may affect risk taking mainly by shifting attention to specific outcomes rather than causing misperception of probabilities. In line with this, in a second study we find evidence that dispositional optimism is related to elicited parameters of rank dependent utility theory suggesting thatfocusingmay be among the psychological determinants of decision weights. Finally, we corroborate our findings with process data related to focusing showing that optimists tend to remember more and attend more to good outcomes and this in turn affects their risk taking.
Keywords: D91; C91; D81; D01; 330; Risk taking behavior; optimism; preference measure